(untitled) (Journal of Global Accounting, 2024)
The study examined the effect of pressure as a fraud risk factor for fraudulent financial reporting in Nigerian deposit money banks. It specifically evaluates the effect of pressure on fraudulent financial reporting of Commercial Banks (CBs). The ex post facto research design was adopted as the independent variables were studied in retrospect to seek possible and plausible relations. The population comprised all Commercial Banks listed on the Nigerian Exchange Group (NGX) as at the end of 2022. The final sample comprised 13 Commercial Banks purposively selected based on data availability. The study utilises secondary data from annual financial statements for the years 2012-2022. The data were analyzed using descriptive, i.e., mean, standard deviation, normality tests, et cetera. and inferential statistical analyses. The hypotheses were tested using the random effects model. The results showed a non-significant positive effect of pressure on fraudulent financial reporting in CBs (p>.05). Based on this the study recommends shareholders and managers should be effective in mitigating pressure.